The Influence of Product Variation and Product Quality on Consumer Loyalty with Consumer Satisfaction as an Intervening Variable in Hand-drawn Batik - Hadita, Hadita; Navanti, Dovina (Dinasti Publisher, 2024)
Article on the influence of product variation and product quality on consumer loyalty with consumer satisfaction as an intervening variable in hand-drawn batik. The purpose of writing this article is to determine the influence of product variation and product quality on consumer satisfaction and consumer loyalty in hand-drawn batik. The research method used is quantitative descriptive. The analysis tool used in this study is SEM SmartPLS 4.1.0.0 The sampling technique uses simple random sampling. The data used in this study are primary data. The population in this study was 214 respondents, with a research sample of 100 respondents, obtained from questionnaires distributed and filled out by consumers who use hand-drawn batik. The tests conducted in this study are Validity Test, Reliability Test, Inner Model, Outer Model and Hypothesis Test. The results of this article are: 1) Product variety has a positive and significant effect on customer satisfaction; 2) Product quality has a positive and significant effect on customer satisfaction; 3) Product variety has no effect and is not significant on customer loyalty; 4) Product quality has no effect and is not significant on customer loyalty; 5) Customer satisfaction has a positive and significant effect on customer loyalty; 6) Product variety has no effect and is not significant on customer loyalty through customer satisfaction; and 7) Product quality has no effect and is not significant on customer loyalty through customer satisfaction